2012
DOI: 10.1371/journal.pntd.0001632
|View full text |Cite
|
Sign up to set email alerts
|

Linking Oviposition Site Choice to Offspring Fitness in Aedes aegypti: Consequences for Targeted Larval Control of Dengue Vectors

Abstract: BackgroundCurrent Aedes aegypti larval control methods are often insufficient for preventing dengue epidemics. To improve control efficiency and cost-effectiveness, some advocate eliminating or treating only highly productive containers. The population-level outcome of this strategy, however, will depend on details of Ae. aegypti oviposition behavior.Methodology/Principal FindingsWe simultaneously monitored female oviposition and juvenile development in 80 experimental containers located across 20 houses in Iq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 55 publications
5
53
1
Order By: Relevance
“…We also assumed the transition from normal to "hot" environments could further decrease survival (p 3 < p 2 ) based on observations from experiments were Ae aegypti larval mortality increased and then decreased following environmental disturbances (Agudelo-Silva & Spielman 1984; Wilson et al 1990). Using the estimate for the product of larval survival and fecundity ( , Table S1) we were able to estimate the fecundity for normal ( 3.42) and "hot" ( 6.84) environments under the assumption of a fecundity-survival trade-off (Stearns 2000), which is plausible assumption for Ae aegypti (Wong et al 2012). The fecunditysurvival trade-off assumes the product of fecundity and larval survival to be constant ( ).…”
Section: Parametersmentioning
confidence: 99%
“…We also assumed the transition from normal to "hot" environments could further decrease survival (p 3 < p 2 ) based on observations from experiments were Ae aegypti larval mortality increased and then decreased following environmental disturbances (Agudelo-Silva & Spielman 1984; Wilson et al 1990). Using the estimate for the product of larval survival and fecundity ( , Table S1) we were able to estimate the fecundity for normal ( 3.42) and "hot" ( 6.84) environments under the assumption of a fecundity-survival trade-off (Stearns 2000), which is plausible assumption for Ae aegypti (Wong et al 2012). The fecunditysurvival trade-off assumes the product of fecundity and larval survival to be constant ( ).…”
Section: Parametersmentioning
confidence: 99%
“…They exhibit complex oviposition choices depending on, conspecific density (Suleman and Shirin 1981; McCrae 1984; Laurence and Pickett 1985; Reiskind and Wilson 2004), predators (Chesson 1984; Blaustein et al 2005) and detritus amount (Edgerly et al 1998; Wong et al 2011, 2012), within oviposition sites (Yee and Juliano 2006, Yee et al 2007a). Several species demonstrate strong oviposition preferences, for sites where the bacteria upon which larvae feed are abundant (Walker et al 1991; Allan and Kline 1995; Navarro et al 2003; Trexler et al 2003; Ponnusamy et al 2010) a preference often mediated via chemical cues (Hazard et al 1967; Allan and Kline 1995; Sant’ana et al 2006; Ponnusamy et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that biotic factors influence the behavior of invertebrate females when choosing where to lay their eggs (Craig et al 1989, Machado & Oliveira 2002, Wong et al 2012. For breeding lady beetle females, resource availability (i.e., aphid presence on the plants) is an important cue to stimulate oviposition (Evans & Dixon 1986, Seagraves 2009).…”
Section: Discussionmentioning
confidence: 99%